O19 Late-window aspiration thrombectomy for anterior Acute Ischemic Stroke: subset analysis for COMPLETE Study. (29th August 2022) - Hassan, AE; Fifi, JT; Zaidat, OO
Abstract : Introduction: The purpose of this analysis was to evaluate safety and performance of late-window aspiration thrombectomy (> 6 hours onset to puncture) in patients with acute ischemic stroke (AIS) in real-world setting. Methods: This subset analysis of a global prospective multicenter registry (COMPLETE) captured data from all patients with anterior circulation LVO, pre-stroke mRS of 0–1, and ASPECTS ≥ 6 who underwent late-window aspiration thrombectomy with the Penumbra System. Primary endpoints were successful revascularization (mTICI 2b-3) post-procedure, good functional outcome at 90 days (mRS 0–2), and all-cause mortality at 90 days. Results: Of 650 patients enrolled across 42 US and European centers, 167 (mean age 68.4, 56.3% female) were included in this analysis. Median NIHSS was 12 (IQR 7–17), median ASPECT Score was 8 (IQR 7–9), and median time from onset to mTICI2b-3 first reached was 11.1 hrs [IQR 8.1–15.3]. Post-procedure mTICI 2b-3 rate was 83.2% (139/167), 90-day mRS 0–2 rate was 55.4% (87/157), and 90-day all-cause mortality rate was 14.4% (24/167). Symptomatic ICH occurred in 4.2% (7/167) and procedure-related SAEs in 5.4% (9/167) of patients. No device-related SAE were observed. For the DAWN and DEFUSE-3 medical management arms, the 90-day mRS 0–2 rates were 13% (13/99) and 17% (15/90), respectively, and the 90-day all-cause mortality rates were 18% (18/99) and 26% (23/90), respectively. Conclusions: Late-window aspiration thrombectomy with Penumbra System is safe and effective for patients with anterior circulation stroke. Our study reports rates of good functional outcome that compare favorably to the DAWN and DEFUSE-3 medical management arms. References: Nogueira Rg et al. Dawn Trial Investigators. Thrombectomy 6 to 24 Hours after Stroke with a Mismatch between Deficit and Infarct. N Engl J Med. 2018 Jan 4;378 (1):11–21. DOI: 10.1056/NEJMOA1706442. EPUB 2017 Nov 11. PMID: 29129157. Albers GW et al . Defuse 3 Investigators. Thrombectomy for Stroke at 6 To 16 Hours with Selection by Perfusion Imaging. N Engl J Med. 2018 FEB 22;378 (8):708–718. DOI: 10.1056/NEJMOA1713973. EPUB 2018 Jan 24. PMID: 29364767; PMCID: PMC6590673. Do you have any conflict of interest to declare? : Yes Conflict of Interest Statement: Zaidat: Grant/research support: Genentech, Medtronic Neurovascular, Stryker; Consultant: Codman, Medtronic Neurovascular, National Institutes of Health (NIH) StrokeNet, Penumbra, Stryker. Other financial or material support: Honoraria: Codman, Medtronic Neurovascular, Penumbra, Stryker. Expert witness. Ownership interest: Galaxy Therapeutics, LLC. Fifi: Grant/research support: Viz.ai. Consultant: Microvention, Stryker, Cerenovus, Penumbra. Other financial or material support: Ownership interest: Imperative Care. DSMB: MIVI, Serenity, Magneto. Hassan: Consultant/Speaker: Medtronic, Microvention, Stryker, Penumbra, Cerenovus, Genentech, GE Healthcare, Scientia, Balt, Viz.ai, Insera therapeutics, Proximie, NeuroVasc, NovaSignal, Vesalio, Rapid Medical, Imperative Care and Galaxy Therapeutics; Principal Investigator: COMPLETE study – Penumbra, LVO SYNCHRONISE – Viz.ai; Steering Committee/Publication committee member: SELECT, DAWN, SELECT 2, EXPEDITE II, EMBOLISE, CLEAR, ENVI, DELPHI; DSMB – COMAND trial.